Initial Impact of Father Empowerment Model on Knowledge and Perception of Attitudes Toward Stunting Prevention in the Working Area of Talang Banjar Primary Health Center, Jambi City - Gina Sonia; Erny Kusdiyah; Denok Tri Hardiningsih; Nuriyah .; Anggelia Puspasari (CV. ITTC INDONESIA, 2026)
Background: Stunting remains a significant health problem in Jambi city, with Talang Banjar Primary Health Center recording the highest Number of cases (113 children) in 2024. Fathers’ involvement in stunting prevention is often overlooked despite their strategic role in family decision-making. Objective: This study aimed to analyze the initial impact of father empowerment model on knowledge and perception of attitudes toward stunting prevention in the working area of Talang Banjar Primary Health Center, Jambi City. Methods: This quasi-experimental study used a one-group pretest-posttest design involving 40 fathers of children aged 0-59 months. The intervention was a one-day workshop on father empowerment for stunting prevention. Knowledge was measured using a 10-item true/false questionnaire, while perception of attitudes was measured using a 10-item Likert scale (5 points). Data were analyzed using Wilcoxon Signed Rank Test and paired t-test. Results: The intervention significantly improved fathers’ knowledge (p < 0.001; r = 0.86), with the mean score increasing from 77.50 to 92.25. Perception of attitudes also improved significantly (p < 0.001; d = 1.403), with the mean score increasing from 74.95 to 84.55. Conclusions: The father empowerment model through a one-day workshop provided a significant positive initial impact on fathers’ knowledge and perception of attitudes toward stunting prevention in the working area of Talang Banjar Primary Health Center, Jambi City.